Propuesta de intervención urbana paisajística del borde del Río Bascún en Baños de Agua Santa - Carrillo Vieira, Alejandra Estefanía (2025)
The research project focuses on the issue of unplanned urban growth and the lack of natural public spaces in Banos de Agna Santa, specifically along the Basctin River. These problems have negatively impacted both the fluvial and natural ecosystems and the quality of life of the local inhabitants. To address this situation, the project proposes the creation of natural public spaces and the incorporation of new activities and services along the Bascim River, aiming to restore the balance between the city and its natural environment. The methodology includes a review of theories and concepts related to the relationship between the river and the city, public spaces, and green and blue infrastructure. In addition, it involves a detailed analysis of intervention strategies, the current state of the BascUti Riverbank, its phenomenological, structural, and urban systems characteristics, as well as the current state of local flora and fauna. The intervention proposal is focused on creating inclusive, sustainable, and connected spaces and activities to improve the quality of life of the inhabitants, preserve biodiversity, and address the particularities of the local environment identified in the site analysis.